2021
DOI: 10.1177/2333721421992996
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Computer Engagement in Older Adults with Dementia

Abstract: Objectives: Two pilot studies aimed to determine the effects of individual computer engagement on behavioral health outcomes in individuals with dementia. The focus was on participants’ mental health, challenging behaviors, antipsychotic medications, and professional caregiver stress. Methods: Two pilot randomized control trials were conducted. First trial involved residents with advanced dementia in a long-term care facility. The second trial involved residents with mild dementia in an assisted living setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Five (5) were women A pet robot PARO designed to interact with residents and stimulate them Robotics Interactions; Engagement; Acceptability Residents exhibited verbal and non-verbal reactions during the intervention. It was perceived as useful because it is comforting, entertaining, creates interest, and interacts with residents Sautter et al [ 51 ] 2021 Benefits of Computer Engagement in Older Adults with Dementia United States Quantitative RCT Twenty-eight (28) residents Touch-screen computer platform “It’s Never Too Late” providing the opportunity to personalize computer applications to enhance social connection, facilitate entertainment, and implement cognitive training through various brain fitness programs Interactive screen Emotional wellbeing by systolic blood pressure; Behaviors; Medication use The intervention has significantly improved residents’ well-being and significantly decreased their systolic blood pressure No significant challenging behaviors or the use of antipsychotic medications were observed Scerri et al [ 40 ] 2021 Formal caregivers’ perceptions and experiences of using pet robots for persons living with dementia in long-term care: A meta-ethnography Malta Qualitative, meta-ethnography Eight (8) studies conducted with LTC staff A pet robot designed to interact with residents and stimulate them Robotics Behavioural symptoms; Social connectedness The intervention was perceived as useful in reducing agitation, restlessness and associated behavioural symptoms, as well as to initiate social connectedness and to evoke old memories and reduce loneliness Sultana et al [ 28 ] 2021 Virtual Reality Experience Intervention May Reduce Responsive Behaviors in Nursing Home Residents with Dementia: A Case Series Canada single site case series Twenty-four (24) residents, mean age of 85.8 years. Most of them were female Virtual reality experience intervention providing interactive and immersive customized three-dimensional visual and auditory experiences Virtual Reality Depression; Med...…”
Section: Resultsmentioning
confidence: 99%
“…Five (5) were women A pet robot PARO designed to interact with residents and stimulate them Robotics Interactions; Engagement; Acceptability Residents exhibited verbal and non-verbal reactions during the intervention. It was perceived as useful because it is comforting, entertaining, creates interest, and interacts with residents Sautter et al [ 51 ] 2021 Benefits of Computer Engagement in Older Adults with Dementia United States Quantitative RCT Twenty-eight (28) residents Touch-screen computer platform “It’s Never Too Late” providing the opportunity to personalize computer applications to enhance social connection, facilitate entertainment, and implement cognitive training through various brain fitness programs Interactive screen Emotional wellbeing by systolic blood pressure; Behaviors; Medication use The intervention has significantly improved residents’ well-being and significantly decreased their systolic blood pressure No significant challenging behaviors or the use of antipsychotic medications were observed Scerri et al [ 40 ] 2021 Formal caregivers’ perceptions and experiences of using pet robots for persons living with dementia in long-term care: A meta-ethnography Malta Qualitative, meta-ethnography Eight (8) studies conducted with LTC staff A pet robot designed to interact with residents and stimulate them Robotics Behavioural symptoms; Social connectedness The intervention was perceived as useful in reducing agitation, restlessness and associated behavioural symptoms, as well as to initiate social connectedness and to evoke old memories and reduce loneliness Sultana et al [ 28 ] 2021 Virtual Reality Experience Intervention May Reduce Responsive Behaviors in Nursing Home Residents with Dementia: A Case Series Canada single site case series Twenty-four (24) residents, mean age of 85.8 years. Most of them were female Virtual reality experience intervention providing interactive and immersive customized three-dimensional visual and auditory experiences Virtual Reality Depression; Med...…”
Section: Resultsmentioning
confidence: 99%
“…Studies generally reported good internal consistency of outcome measures used (α = .64–.95), though consistency was not available for six outcomes. Data from 11 outcomes (3 studies), were insufficient to be included in the meta-analysis ( Halek et al, 2020 ; Sautter et al, 2021 ; Zwijsen et al, 2015 ). In total, 17 outcomes (7 studies) were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the distinct categories, all organisation focused interventions also included caregiver education. Insufficient data was reported for three interventions ( n = 3), to be included in the meta-analysis ( Halek et al, 2020 ; Sautter et al, 2021 ; Zwijsen et al, 2015 ). In total, 12 interventions (from 7 studies) were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%